Dental rehabilitation of a rare Hallermann-Streiff Syndrome with Olygodontia : a case report = Rehabilitación dental de un caso raro de Síndrome de Hallermann-Streiff con Oligodoncia : reporte de un caso - Keskin, Gül
Hallermann-Streiff syndrome (HSS) is a rare oculomandibulofacial discephaly with hypotrichosis that occurs as a sporadic mutation. It is characterized by abnormal findings especially in head and face. Dental anomalies occur in 50-80% of the patients. In this case report, facial-oral findings and the existing dental anomalies of the syndrome in a 6-year-old male patient diagnosed with HSS were identified. Dental rehabilitation and a 12-month follow-up of the patient were reported. Each case presented with this rare syndrome may contribute to the literature to determine the prognosis of the disease and to take protective and preventive measures.